3-Methyl-4-{(E)-[4-(methylsulfanyl)-benzylidene]amino}-1H-1, 2,4-triazole-5(4H)-thione - Hegde, Gurumurthy; Sarojini, B. K.; Manjula, P. S.; Kour, Dalbir; Gupta, Vivek K.; Kant, Rajni (International Union of Crystallography, 2013)
In the title molecule, C11H12N4S2, the dihedral angle between the triazole and benzene rings is 21.31 (5). A weak intramolecular C—H S hydrogen bond generates an S(6) ring motif. In the crystal, pairs of N—H S hydrogen bonds form inversion dimers. In addition, – interactions are observed between the benzene rings, with a centroid–centroid separation of 3.7599 (11) A°.